2019
DOI: 10.20546/ijcmas.2019.804.015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of INM on Growth and Yield of Maize (Zea mays) Crop in Central Plain Zone of Uttar Pradesh

Abstract: Maize (Zea mays L.) is one of the most important cereal crop, next to rice and wheat and is used as a food for human and feed for animals. This crop has been developed into a multi dollar business in countries viz. Thiland,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…There is no influence of applied amendments on seed germination and therefore no significant variation in plant population was observed. These findings are related to the findings of Mishra et al [13].…”
Section: Plant Populationsupporting
confidence: 91%
“…There is no influence of applied amendments on seed germination and therefore no significant variation in plant population was observed. These findings are related to the findings of Mishra et al [13].…”
Section: Plant Populationsupporting
confidence: 91%
“…Organics besides release their own nutrient might have increase in the nutrient use efficiency of applied inorganic fertilizers. Patil et al (2017) [12] , Kumar et al (2018) [6] and Mishra et al (2019) [10] also reported similar findings.…”
Section: Grain Yield (Kg Ha -1 )mentioning
confidence: 59%
“…Maize (Zea mays L.) is one of the important cereal crops belonging to the Poaceae family, which ranked third after wheat and rice crops in terms of productivity, production and cultivated area in the world [1]. It is a short duration, quick growing and widely grown crop with high potential, there are no cereal crops with such an immense potentiality, so it is called as "queen of cereals" [2].…”
Section: Introductionmentioning
confidence: 99%